REALITAS PERILAKU BERAGAMA KOMUNITAS TUKANG SAMPAH DI KELURAHAN GUNUNGSARI KECAMATAN RAPPOCINI KOTA MAKASSAR - Muslimin, Abdul Azis; Baharuddin, Baharuddin (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
The purpose of this research to review and analyze the behavior of religious community garbage man , and role of stakeholders terahadap religious training for the poor , especially the garbage men in Rappocini in Gunung Sari village cider in the City of Makassar. Type this research qualitative analysis method use phenomenology descriptive approach.Target this report is written by observing work garbage man in the afternoon until night car come when container, and there are around 13 one who fill from garbage exertion container taken from house to house in their respective work areas in several RT/RW. Types of data on used covering, primary data, the data obtained in the field through interviews deeply to the informants.Secondary data, the data obtained of documents that is in the government Gunung Sari Makassar City. Focus group discussion (FGD ), this activity was carried out under the coordination of sub-district government Gunung Sari kecamatan rappocini makassar city. The research results show that religious behavior community garbage man in gunung sari Kecamataan Rappocini City of Makassar very pragmatic characterized by simple once they perceive. Religious working as a trash is an option that inevitable for existence of poor people like this be punctuated the urban community because the informal sector they touch highly improbable touched by the bourgeois or economic as well as the conglomerate top, and the presence of stakeholders and the focus of intense kajiannya to social issues is really needed in order to meet the needs of their spiritual.Muhammadiyah University as a college, characterized by religious should make the very sent Tridarma College with had expanded coaching, religious communities like this let alone college were inside sub-districts Rappocini is.